Édito - L'autorité et le pouvoir éducatifs à l'épreuve des politiques d'éducation - Camille Roelens; Stéphan Mierzejewski (Nantes Université, 2022)
This dossier addresses the issue of the recomposition of power and authority relationships within the school system by examining the relationships at work between the different actors of the school institution responsible for defining, supervising and implementing public policies that are supposed to respond to the challenges of the time. By focusing on management, supervisory or training personnel, and by emphasizing the multi-referentiality of the sciences of education and training, the texts in this file take up this question at its roots by considering its implications on the most global scale, as well as its most practical and daily professional incidences. Seized from the situation of those who, in the educational system, are supposed to embody it first and foremost, the conditions and concrete modalities of the metamorphosis of institutional authority reveal how the exercise of the corresponding responsibilities is put to the test by contemporary public policies of accountability and the batch of uncertainties and paradoxical injunctions that they bring with them.